Legal Protection for Contract Workers in the Perspective of Labor Law - Arifuddin, A.Muhammad Yusuf Aulia; Afnina, Afnina; Siti Syafiqah Shada (Innovative: Journal Of Social Science Research, 2025)
Contract workers are a group of workers who are widely used by companies to meet labor needs within a certain period of time. The contract work system is considered flexible and efficient from the employer's point of view, but often creates uncertainty for workers. Although the Indonesian Labor Law has regulated the rights and obligations of contract workers, its implementation in the field still faces various obstacles. Some of the problems that arise are related to the period of employment agreements that are often illegally extended, lack of access to social security, and the weak bargaining position of contract workers in industrial relations. This research aims to comprehensively analyze legal protection for contract workers in the perspective of national labor law. The approach used is a normative legal approach, with the method of literature study and analysis of applicable laws and regulations, including Law Number 13 of 2003 concerning Manpower and its amendments in the Job Creation Law. The results show that there is a discrepancy between legal norms and practices that occur in the field, which is caused by weak supervision, low legal awareness of employers, and not optimal role of labor institutions and trade unions. Therefore, it is necessary to strengthen the labor inspection system, increase legal education for workers, and revise regulations that are more in favor of protecting the rights of contract workers in order to create social justice in employment relations.Keywords: Legal Protection, Contract Workers, Labor Law, Worker’s Right, Legal Uncertainty